Functional diversity of leaf nitrogen concentrations drives grassland carbon fluxes. (7th January 2014) - Milcu, Alexandru; Roscher, Christiane; Gessler, Arthur; Bachmann, Dörte; Gockele, Annette; Guderle, Markus; Landais, Damien; Piel, Clément; Escape, Christophe; Devidal, Sebastien; Ravel, Olivier; Buchmann, Nina; et al.
Abstract Little is known about the role of plant functional diversity for ecosystem‐level carbon (C) fluxes. To fill this knowledge gap, we translocated monoliths hosting communities with four and 16 sown species from a long‐term grassland biodiversity experiment ('The Jena Experiment') into a controlled environment facility for ecosystem research (Ecotron). This allowed quantifying the effects of plant diversity on ecosystem C fluxes as well as three parameters of C uptake efficiency (water and nitrogen use efficiencies and apparent quantum yield). By combining data on ecosystem C fluxes with vegetation structure and functional trait‐based predictors, we found that increasing plant species and functional diversity led to higher gross and net ecosystem C uptake rates. Path analyses and light response curves unravelled the diversity of leaf nitrogen concentration in the canopy as a key functional predictor of C fluxes, either directly or indirectly via LAI and aboveground biomass.